Formal Verification Proof

Hello, I am confused on much of the following...

Determine if the following formulas are satisfiable. P' is the negation of P.

(P→Q)→(Q'→P') <-- I read this as being P=true then Q=true, Q'=false then P'=false, so Q=true implies Q'=false???

(Q→R)→((P→Q)→(P→R)) <-- I read this as (Q→R)→(Q→R) because (P→Q)→(P→R) = (Q→R) right???

(P∧Q)→ (P∨Q) <-- AND versus OR ???

(Q→R)→((P∨Q)→(P∨R)) <--

I am probably going about this incorrectly... any help would be greatly appreciated.

TIA!